GA₃와 Streptomycin 복합처리가 블랙베리 무핵화 유기에 미치는 영향 - 정혜민(HeaMin Jeong); 김은주(Eun Ju Kim); 최동근(Dong Geun Choi) (Weon'ye gwahag gi'sulji, 2018)
This study was carried out to determine the effects of various application times and concentrations of GA3 with streptomycin (SM) on fruiting, the rate of seedless drupelet formation, and fruit quality in ‘Super’ blackberry. Flower clusters were sprayed with GA3 at 12.5, 25.0, 50.0, and 100 mg·L-1 combined with 200 mg·L-1 SM. Single treatments were conducted using a hand sprayer at 30% and 50% of full bloom (FB), and duplicate treatments were conducted by spraying twice at 30% and 50% FB, respectively. The application of GA3 + SM on flower clusters had no effect on fruit set, harvest time, or various fruit qualities (fruit firmness and SSC). The rate of seedless drupelet formation for control fruit was approximately 2.5%. Under single treatment, the rate of seedless drupelet formation was higher at a spray time of 50% FB compared with 30% FB treatment, and the rate was highest at a GA concentration of 25.0 mg·L-1. The highest seedless drupelet rate was 56.7% for fruits sprayed twice at 30% and 50% FB with GA + SM. Single treatment at 30% FB with 100 mg·L-1 GA3 + SM induced 22.2-35.2% seedless drupelet formation, whereas single treatment at 50% FB and duplicate treatments at 30 and 50% FB led to the formation of seedless drupelets at a rate of 31.6-42.2% and 22.6-56.7%, respectively. Among GA concentrations, 25.0 mg·L-1 GA3 treatment led to the highest rate of seedless drupelet formation (35.3-56.7%). The occurrence of malformed berries was higher in the GA + SM treatment group than in the control, and the incidence increased with increasing GA concentration. GA3 + SM treatment slightly increased fruit length but had no effect on fruit diameter. KCI Citation Count: 1